Microbiological Analysis of Drinking Water of Kathmandu Valley - Prasai, Tista; Lekhak, Binod; Joshi, Dev Raj; Baral, Madhav Prasad (Scientific World, 2010)
Drinking water quality assessment in Kathmandu valley has always been crucial with reference to public health importance. A study was conducted to evaluate the quality of drinking water of the valley. A total of 132 drinking water samples were randomly collected from 49 tube wells, 57 wells, 17 taps and 9 stone spouts in different places of Kathmandu valley. The samples were analyzed for microbiological parameters. Total plate and coliform count revealed that 82.6% and 92.4% of drinking water samples found to cross the WHO guideline value for drinking water. During the study, 238 isolates of enteric bacteria were identified, of which 26.4% were Escherichia coli, 25.6% were Enterobacter spp, 23% were Citrobacter spp, 6.3% were Pseudomonas aeruginosa, 5.4% were Klebsiella spp, 4.0% were Shigella spp, 3.0% were Salmonella typhi, 3.0% were Proteus vulgaris, 3.0% were Serratia spp and 1.0% were Vibrio cholerae . Key words: Drinking water; Public health; Coliform; Bacteria. DOI: 10.3126/sw.v5i5.2667 Scientific World, Vol. 5, No. 5, July 2007 112-114